Faktor-faktor yang mempengaruhi keberlangsungan usaha UMKM di Yogyakarta - Ayem, Sri; Hernindya, Nanda Rachma (Universitas Negeri Surabaya, 2025)
This study aims to identify the factors that influence the sustainability of businesses in Yogyakarta. The research employs a quantitative approach with a sample of 98 respondents, consisting of micro, small, and medium-sized enterprises (MSMEs) in the Yogyakarta region, using accidental sampling as the sampling technique. The variables analyzed in this study include understanding the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM) and the use of online wallets. The results of the study indicate that both understanding SAK-EMKM and the use of online wallets have a positive impact on business sustainability. These findings suggest that enhancing understanding of accounting standards and utilizing digital payment technologies play an essential role in supporting the sustainability of MSMEs in Yogyakarta.